Information and communication technology for agriculture in the People Republic of China. (Metro Manila, Philippines Asian Development Bank, 2019)
The analysis focuses on e-commerce in rural areas of the country and provides policy recommendations to promote the use of ICT in the agricultural supply chain. The report documents the trends in ICT application by farmers and its impact on income and livelihood. It also identifies the major constraints to and enabling factors for such ICT applications.
Keywords: Agricultural resources -- Management -- Technology innovation; Agriculture -- Economic aspects -- China; Electronic books